Increased Explicitness of Assessment Criteria: Effects on Student Motivation and Performance - Balan, Andreia; Jönsson, Anders (Frontiers in Education, 2018)
The purpose of this study was to investigate the effects of increased explicitness of assessment criteria on students’ performance and motivation. Successive levels of explicitness, from feedback based on (implicit) criteria to a combination of exemplars and explicit criteria, were implemented in eight classes at four schools (n = 153 students, 12-13 years old) during four teaching sequences in science. Data was collected on: (a) student performance through knowledge tests, (b) student motivation (self-efficacy, goal orientations, and self-regulation) through questionnaires, and (c) perceived clarity of goals and criteria through “exit tickets”. Findings show that student performance improved from pre-, to post-tests at all schools (effect sizes from .82 to 1.38), but not in relation to the level of explicitness. There was also an increase in self-efficacy for low-performing students, but, again, not in relation to explicitness. These changes are instead assumed to be an effect of the formative feedback provided as part of the intervention. The only change related to the level of explicitness, was an increase in self-regulation scores by high-performing students when having access to both exemplars and explicit criteria. Findings therefore suggest that low to medium levels of explicitness in assessment have no discernable effects on students’ performance or motivation.